2015
DOI: 10.3807/josk.2015.19.3.217
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Ni/Cu Metallization to Investigate an Adhesive Front Contact for Crystalline-Silicon Solar Cells

Abstract: Developing a metallization that has low cost and high efficiency is essential in solar-cell industries, to replace expensive silver-based metallization. Ni/Cu two-step metallization is one way to reduce the cost of solar cells, because the price of copper is about 100 times less than that of silver. Alkaline electroless plating was used for depositing nickel seed layers on the front electrode area. Prior to the nickel deposition process, 2% HF solution was used to remove native oxide, which disturbs uniform ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…They identified that Ni silicides (Ni 2 Si and NiSi) could be detected in cells for which a strong pull force was measured but was absent in cells with a very low pull force. This result appears to confirm the requirement for Ni silicide formation for strong contact adhesion; however, the reason for why the silicide formed sometimes and not at other times with post‐plating annealing was unclear.…”
Section: Challenges For Copper‐plated Silicon Solar Cellssupporting
confidence: 62%
“…They identified that Ni silicides (Ni 2 Si and NiSi) could be detected in cells for which a strong pull force was measured but was absent in cells with a very low pull force. This result appears to confirm the requirement for Ni silicide formation for strong contact adhesion; however, the reason for why the silicide formed sometimes and not at other times with post‐plating annealing was unclear.…”
Section: Challenges For Copper‐plated Silicon Solar Cellssupporting
confidence: 62%
“…ITO, ZnO (sputtered, EIA15), B‐doped ZnO (Fan15), and ZnO:Al (EIA15) were applied to the air/TCO/ITO/Si substrate structure as TCO materials. In the case of the ITO/ITO/Si substrate structure, the doping concentration of the top ITO layer was varied from 1.7 × 10 to 4.9 × 10 20 cm −3 , and the doping concentration of the bottom ITO was fixed at 6.1 × 10 20 cm −3 . The insulator and TCO thickness were optimized to maximize the generation current density in the Si substrate.…”
Section: Methodsmentioning
confidence: 99%
“…Passivated emitter solar cells (PESCs), passivated emitter and rear cells (PERCs), interdigitated back contact cells (IBCs), passivated emitter rear locally diffused cells (PERLs), and buried contact solar cells (BCSCs). [13][14][15][16][17][18][19][20] However, as shown in Figure 1, heterojunction with intrinsic thin-layer (HIT) solar cells do not have an insulation material for ARC layer since the TCO layer acts as an ARC layer. [21][22][23] To maximize the destructive interference at a specific wavelength, the materials and thickness of the TCO layer must be chosen carefully.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation